The utility of emergency department physical therapy and case management consultation in reducing hospital admissions. Issue 5 (26th June 2020) - Gurley, Kiersten L.; Blodgett, Maxwell S.; Burke, Ryan; Shapiro, Nathan I.; Edlow, Jonathan A.; Grossman, Shamai A
Abstract: Background: A significant number of patients who present to the emergency department (ED) following a fall or with other injuries require evaluation by a physical therapist. Traditionally, once emergent conditions are excluded in the ED, these patients are admitted to the hospital for evaluation by a physical therapist to determine whether they should be transferred to a sub‐acute rehabilitation facility, discharged, require services at home, or require further inpatient care. Case management is typically used in conjunction with a physical therapist to determine eligibility for recommended services and to aid in placement. Objective: To evaluate the benefit of using ED‐based physical therapist and case management services in lieu of routine hospital admission. Methods: Retrospective, observational study of consecutive patients presenting to an urban, tertiary care academic medical center ED between December 1, 2017, and November 30, 2018, who had a physical therapist consult placed in the ED. We additionally evaluated which of these patients were placed into ED observation for physical therapist consultation, how many required case management, and ED disposition: discharged home from the ED or ED observation with or without services, placed in a rehabilitation facility, or admitted to the hospital. Results: During the 12‐month study period, 1296 patients (2.4% of the total seen in the ED) were assessed by a physical therapist. The mean age was 75.5 ± 15.2 and 832 (64.2%) were female. Case management was involved in 91.8% of these cases. The final patient disposition was as follows: admission 24.3% (95% CI = 22.1–26.7%), home discharge with or without services 47.8% (95% CI = 45.1–50.5%), rehabilitation (rehab) setting 27.9% (95% CI = 25.6%–30.4). The median (interquartile range) time in observation was 13.1 (6.0–20.3), 9.9 (1.8–15.8), and 18.4 (14.1–24.8) hours for patients admitted, discharged home, or sent to rehabilitation ( P  < 0.001). Among the 979 patients discharged home or sent to rehabilitation, 17 (1.7%) returned to the ED within 72 hours and were ultimately admitted. Conclusion: Given that the standard of care would otherwise be an admission to the hospital for 1 day or more for all patients requiring physical therapist consultation, an ED‐based physical therapy and case management system serves as a viable method to substantially decrease hospital admissions and potentially reduce resource use, length of hospital stay, and cost both to patients and the health care system.